Analysis of the role of islamic religious education teachers in enhancing students’ critical thinking in moral learning based on the merdeka curriculum at SMP Muhammadiyah 1 Sukoharjo - Sulistiawati Mawarni; Isfihani; Iffah Mukhlisah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) teachers in enhancing students’ critical thinking skills in moral learning based on the Merdeka Curriculum at SMP Muhammadiyah 1 Sukoharjo in the 2024/2025 academic year. The focus lies on how teachers carry out their roles as demonstrators, classroom managers, mediators, and evaluators, along with the supporting and inhibiting factors influencing these roles. A qualitative approach with a case study design was employed, and data were collected through classroom observations, in-depth interviews with teachers, students, and the principal, as well as document analysis of teaching modules. The findings show that the IRE teachers’ roles are relatively effective. The Grade VII teacher was categorized as Good with an average score of 3.5, while the Grade VIII teacher was Very Good with an average score of 3.6. The roles of demonstrator and classroom manager were well executed, while mediator and evaluator roles need improvement. Supporting factors include teachers’ awareness of critical thinking, principal support, comprehensive modules, and positive student perceptions. Inhibiting factors include the dominance of lecturing, limited facilitation of discussions, and uneven student participation. The study implies that strengthening critical thinking in IRE requires comprehensive teacher roles, institutional support, and innovative teaching strategies.